(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
This research dealt with the impact of internal control on tax performance using balanced scorecard indicators because of its special importance in improving tax performance and reform. The internal control system is a safety valve for senior management in all organizations, it plays an important role in the regularity and development of work and the fight against corruption To provide reliable and accurate data and information, follow up on compliance with laws, regulations and instructions. The aim of this research is to demonstrate how control affects tax performance and how to adapt internal control components to improve tax performance. In the General Authority for taxes and its branches,. The research resulted in a number of conclusions, most notably the existence of a significant weakness in the risk assessment due to the lack of modern mechanisms and tools to measure, analyze and evaluate risks, in addition to the Authority’s reliance on traditional monitoring and follow-up mechanisms in the audit of tax data, as well as the disproportionate number of taxpayers registered in the tax. With the capabilities of the tax authority and its branches